Impact on sediment yield due to the intensification of tobacco production in a catchment in Southern Brazil - Merten,Gustavo Henrique (2006)
Tobacco production in Southern Brazil has caused a profound impact in the environment, resulting in heavy sediment yields and diminishing water quality. Public programmes have attempted to address these problems by encouraging the implementation of erosion control practices. To evaluate the impact of these programmes, a small rural catchment (1.33km²) in Arvorezinha county, in the state of Rio Grande do Sul, Brazil, has been monitored since 2001. Instruments to automatically monitor flow rate and precipitation were installed in the catchment and sediment has been measured manually using a DH-48 sampler. Despite lower rainfall in 2003, there was a significant increase in the frequency of low and average flow rates, and sediment yield increased 25% in 2003 (91Mg km-2 year-1), compared with 2002 (73Mg km-2 year-1). These results can be explained by a 37.7% increase in the area dedicated to tobacco cultivation in 2003, due to a rise in tobacco prices.